Identification of a differentiation-inducible promoter in the E7 open reading frame of human papillomavirus type 16 (HPV-16) in raft cultures of a new cell line containing high copy numbers of episomal HPV-16 DNA. - Grassmann, K (1996)
Gene expression of human papillomaviruses (HPV) is tightly linked to differentiation processes within the pluristratified epithelium. To analyze changes in the transcription pattern of HPV-16 during epithelial cell differentiation, we established a permanently growing HPV-16 positive cell line, designated KG, from a vulvar intraepithelial neoplasm. KG cells of early passages harbored multiple copies of the HPV-16 DNA as episomes and were able to form a stratified epithelium in an organotypic raft culture system. Analysis of viral gene expression revealed the known transcription pattern of the early region of HPV-16 with the exception of a so far undefined mRNA class with start sites in the E7 open reading frame. Quantitative analysis of primer extension experiments with RNA from KG cells grown in monolayer and raft culture showed a strong induction of this transcript in differentiated KG cells, whereas the level of the mRNAs initiated at the early promoter P97 remained almost constant. Primer extension analyses with four different primers and direct sequencing of the extension product revealed that the differentiation-inducible transcript initiated at a novel promoter with a major start site around nucleotide position 670 (P670) in the E7 open reading frame of HPV-16. Sequence analysis of cDNAs derived from RNA of KG cells grown in raft culture suggested that the transcripts initiated at P670 have a coding potential for an E1E4 fusion protein and for the E5 protein.